PENINGKATAN KETERAMPILAN MEMBACA DAN MENULIS DENGAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MULTIMEDIA UNTUK SEKOLAH DASAR - Diyah Choirina; Riawan Yudi Purwoko; Suyoto (Jurnal Binagogik, 2024)
This research aims: 1) To describe the application of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by multimedia to improve reading and writing skills in class III Javanese language subjects at SDN 1 Kutowinangun, 2) To describe the improvement of reading and writing skills by applying the Cooperative learning model Multimedia-assisted Integrated Reading and Composition (CIRC) in class III Javanese language lessons at SDN 1 Kutowinangun. The type of research used is Classroom Action Research (PTK) through 4 stages, namely the planning, action, observation and reflection stages. The research subjects were class III students at SDN 1 Kutowinangun for the 2022/2023 academic year with a total of 32 students. Test and non-test data collection techniques (interviews, observations, and documentation). Data analysis by calculating the results of reading and writing skills assessments as well as individual evaluation results. The steps of the Cooperative Integrated Reading And Composition (CIRC) model are orientation, organization, concept introduction, exploration and application, publication, and reinforcement and reflection. The results of the first cycle of research on reading skills obtained an average of 46.88% learning completeness while writing skills averaged 45.31%, second cycle reading skills averaged 78.13% while writing skills averaged 71.88 % so it can be concluded that with the correct procedures and using the Cooperative Integrated Reading And Composition (CIRC) learning media model, it can improve the reading and writing skills of class III students at SDN 1 Kutowinangun.